2008
DOI: 10.1007/s10103-008-0555-1
|View full text |Cite
|
Sign up to set email alerts
|

Relieving pain in minor aphthous stomatitis by a single session of non-thermal carbon dioxide laser irradiation

Abstract: This randomized controlled clinical trial was designed to evaluate the efficacy of single-session, non-thermal, carbon dioxide (CO(2)) laser irradiation in relieving the pain of minor recurrent aphthous stomatitis (miRAS) as a prototype of painful oral ulcers. Fifteen patients, each with two discrete aphthous ulcers, were included. One of the ulcers was randomly allocated to be treated with CO(2) laser (1 W of power in de-focused continuous mode) and the other one served as a placebo. Before laser irradiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 26 publications
2
97
0
3
Order By: Relevance
“…Recently, there were a case report and clinical trials showing benefit of immediate pain relief on aphthous ulcers by using CO2 laser at 0.7 to 1.5 W irradiating to the transparent gel. On the basis of no clinical alteration, this was called the non-thermal CO2 irradiation [4][5][6][7] . By comparison with laser ablation for replacing aphthous ulcer with the lasered wound 1,8) , this technique appeared to be non-invasive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there were a case report and clinical trials showing benefit of immediate pain relief on aphthous ulcers by using CO2 laser at 0.7 to 1.5 W irradiating to the transparent gel. On the basis of no clinical alteration, this was called the non-thermal CO2 irradiation [4][5][6][7] . By comparison with laser ablation for replacing aphthous ulcer with the lasered wound 1,8) , this technique appeared to be non-invasive.…”
Section: Introductionmentioning
confidence: 99%
“…These discoveries were like those of a study which was directed by Khademi et al, in which the mending time and agony force were assessed and looked at between a low-level laser gathering and a fake treatment bunch which included separate arrangements of patients. [7,8] De Souza et al led a randomized clinical assessment of LLLT (InGaAlP diode laser, 670 nm, 3 J/cm 2 ) in the treatment of RAS in 15 patients and found that LLLT with a topical steroid diminished agony levels after the principal LLLT session. Be that as it may, the level of decrease was not measurably huge.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a CO2 laser of about 3 W a pulsed CW of (10 -1000 ms and a super pulse of 0.1 -1 ms) is used for the skin treatment such as eliminating a mole, a wart, macule (Gotkin et al, 2009) and wrinkle the aurinasal treatment such as hay fever and allergic rhinitis (Takeno et al, 2009), the eye treatment such as blepharochalasis and droopy eyelid (Rokhsar et al, 2008), and the dental treatment such as section and evaporation of soft tissue, hemostasis, and stomatitis (Zand et al, 2009). The advantages of CO2 laser surgery are alleviation of bleeding, pain and edema, and shortening of operation and recovery time.…”
Section: Medical Applicationsmentioning
confidence: 99%